Parental Roles and Strategies in Shaping the Academic Performance of Homeschooled Learners: A Mixed-Methods Approach - Jesus, Dennis A. De (International Journal of Atharva, 2025)
This study examines the roles and strategies employed by parents to influence the academic performance of homeschooled learners. Utilizing a mixed-methods approach, the research combines surveys of 100 homeschooling parents with in-depth qualitative interviews to analyze parental involvement comprehensively. Conducted between 2022 and 2024 across various communities in the Philippines, the study identifies key strategies such as consistent scheduling, personalized study plans, and emotional support, which significantly enhance learners' academic outcomes. However, parents face challenges, including balancing multiple responsibilities and limited access to teaching resources. The findings emphasize the need to provide parents with adequate training and resources to optimize the benefits of homeschooling.